Training Installation and Configuration Network Computer Simple for Students of Cipta Insani Vocational School Independent - Rino Subekti; Devi Puspitasari; Ghanistantiono Ghanistantiono; Dade Maulana; Erdiek Ardhianto; Muhammad Raihan (International Journal Of Community Service, 2024)
Training installation and configuration network computer simple for students of Cipta Insani Vocational School Independent aiming For increase understanding and skills student in build as well as manage network computer . The method used in devotion This is approach practical through session theory and practice directly , where students given material about the basics network , device hard used , as well as steps installation and configuration . The results of training This show improvement knowledge student about network computer , which is measured through pre-test and post-test, as well bait come back positive from participant about involvement and implementation material . With training this , it is expected student can implement knowledge gained​ in projects at school and in the world of work in the future . The success of this program shown with activity all participants and enthusiasts participant do discussion and results questionnaire satisfaction show by 90.50% of participants satisfied with existence training This Because can increase understanding as well as ability practical student about Network Computer